Teaching, Gender and Labour Market Incentives - David Carroll; Jaai Parasnis; Massimiliano Tani (Institute of Labor Economics (IZA), 2018)
The concentration of women in the teaching profession is widely noted and generally attributed to gender differences in preferences and social roles. Further, gender segregation exists within this profession – women make up almost all of the primary and pre-primary teaching cohorts, while men who choose to become teachers tend to specialise in secondary schooling and administrative roles. To what extent is this gender structure in teaching a response to economic incentives from the labour market? Our research addresses this question by studying the effects of wage structure on the decision to become a teacher. In particular, we ask what the most attractive choice is for a graduate given the wage structure of the previous graduate cohort. We show that the labour market, especially the relative returns to education across occupations for men and women, can explain these vocational choices in the Australian context. Women with bachelor qualifications receive higher returns as teachers, while men with bachelor qualifications receive higher returns in other occupations. In contrast, while both men and women with postgraduate qualifications earn higher returns in other occupations, the difference is consistently smaller for women than men. Women face a lower opportunity cost for becoming a teacher compared to men. A more balanced gender representation among teachers seems unlikely given the existing structure of returns to education, by gender, across professions.
Keywords: I26; J16; J24; J31; 330; occupational segregation; teachers; opportunity cost; decomposition